The Q.S AL-‘ASHR PERSPEKTIF TEORI DOUBLE MOVEMENT FALZUR RAHMAN: DALAM MENANGGAPI FENOMENA BRAINT ROT - Hazmi, M. Hafiz Mauluddin (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2025)
In the era of Society 5.0, the phenomenon of brain rot arises as a result of excessive consumption of shallow content on social media, hindering deep thinking and negatively affecting mental health. Surah Al-‘Ashr offers important insights into understanding this phenomenon through Fazlur Rahman’s theory of double movement, which analyzes the Qur'an in two contexts: micro (the reasons for the revelation) and macro (the socio-historical conditions). This study aims to apply this theory in addressing brain rot in the contemporary age. The research uses a descriptive qualitative approach with a library research method. The theory of double movement is applied to analyze Surah Al-‘Ashr in response to modern challenges, such as brain rot, by integrating traditional and Western thought and providing a critical perspective on global issues. The findings reveal that the first movement encourages us to reflect on how the habit of consuming unproductive content wastes valuable time and harms intellectual capabilities. This phenomenon is similar to the habits of the Arab society during the time of 'Ashr, which often got caught in useless conversations that led to conflict. The second movement in Surah Al-‘Ashr emphasizes the importance of using time wisely, a universal principle that should be applied in daily life. The third verse teaches us to fill our time with beneficial activities, such as having faith, doing good deeds, and advising one another in truth and patience. In the digital context, addiction to shallow content can hinder intellectual development, much like harmful habits from the past. Surah Al-‘Ashr reminds us to use time wisely, focus on activities that enrich intellectual growth, and maintain emotional balance.